Strategi Meningkatkan Prestasi Belajar Siswa pada Pembelajaran PAK Menurut Teori Belajar Konstruktivisme di SMPN 3 Boronadu Gomo Nias - Sergius Lay; Sitepanus Zebua; Natalianoriana Giawa (Journal New Light, 2025)
This scientific work is motivated by low student learning achievement, this occurs because the learning hypothesis applied is less attractive to students. The reason for conducting the testing was to determine a system for further developing student learning achievements in strict Catholic training through the Constructivist learning hypothesis at SMP Negeri 3 Boronadu Gomo, Nias. Case studies and qualitative research are used in this research method. Purposive sampling was used to select the sample for this research. Perception, meeting and documentation are strategies used for information gathering. Through deriving information, presenting information, checking/rectifying information, and drawing conclusions about information, the information is dissected. Instructors and school directors were the subjects of this exploration. By considering the findings of completed assessments, the constructivist learning hypothesis can build students' imagination, attraction and energy in participating in learning both inside and outside the classroom. This is done because the teacher gives students the opportunity to concentrate independently or in groups, and the methodology used by the teacher can be intended for students so that students can easily understand and recall the material they have studied. In the end, the constructivist learning speculation clearly has an impact on student learning achievement or can also improve student learning achievement, especially in heavy Catholic learning at SMP Negeri 3 Boronadu.